Pengelolaan Lingkungan Sekolah Islami terhadap Pembiasaan Ibadah Siswa di SMP IT Washilatun Nazah - Andes Balika, Yesshe (CV. PUSDIKRA MITRA JAYA, 2024)
Objective: This study aims to analyze the impact of Islamic school environment management on students' prayer habits at SMP IT Washilatun Nazah. Methodology: A qualitative approach was employed, utilizing data collection techniques such as observation, interviews, and documentation. Findings: The study reveals that the management of an Islamic school environment positively influences students' prayer habits. This is evident through the provision of adequate prayer facilities, the implementation of religious policies, and the exemplary behavior demonstrated by teachers and staff. Additionally, the reward and punishment system effectively enhances students’ discipline in performing religious practices. However, the study also identifies several challenges, including the lack of family involvement in reinforcing prayer habits at home and the tendency of some students to engage in religious practices only under school supervision. Conclusion: Effective Islamic school environment management can serve as a powerful tool in fostering students’ prayer habits. Nevertheless, stronger synergy between the school and families is necessary to ensure the continuity of religious practices beyond the school setting.